Novel IQCE variations confirm its role in postaxial polydactyly and cause ciliary defect phenotype in zebrafish. Issue 1 (17th October 2019) - Estrada‐Cuzcano, Alejandro; Etard, Christelle; Delvallée, Clarisse; Stoetzel, Corinne; Schaefer, Elise; Scheidecker, Sophie; Geoffroy, Véronique; Schneider, Aline; Studer, Fouzia; Mattioli, Francesca; Chennen, Kirsley; Sigaudy, Sabine; et al.
Abstract: Polydactyly is one of the most frequent inherited defects of the limbs characterized by supernumerary digits and high‐genetic heterogeneity. Among the many genes involved, either in isolated or syndromic forms, eight have been implicated in postaxial polydactyly (PAP). Among those, IQCE has been recently identified in a single consanguineous family. Using whole‐exome sequencing in patients with uncharacterized ciliopathies, including PAP, we identified three families with biallelic pathogenic variations in IQCE . Interestingly, the c.895_904del (p.Val301Serfs*8) was found in all families without sharing a common haplotype, suggesting a recurrent mechanism. Moreover, in two families, the systemic phenotype could be explained by additional pathogenic variants in known genes ( TULP1, ATP6V1B1 ). RNA expression analysis on patients' fibroblasts confirms that the dysfunction of IQCE leads to the dysregulation of genes associated with the hedgehog‐signaling pathway, and zebrafish experiments demonstrate a full spectrum of phenotypes linked to defective cilia: Body curvature, kidney cysts, left–right asymmetry, misdirected cilia in the pronephric duct, and retinal defects. In conclusion, we identified three additional families confirming IQCE as a nonsyndromic PAP gene. Our data emphasize the importance of taking into account the complete set of variations of each individual, as each clinical presentation could finally be explained by multiple genes. Abstract : In this study, we report the confirmation of IQCE as a gene whose defects cause isolated postaxial polydactyly. Whole‐exome sequencing has been applied to three families and revealed biallelic pathogenic variations in IQCE . Further functional analysis using the patient's cells (skin fibroblast) revealed no effect on the formation of the cilia but a mislocalization of the EVC2 and a defective hedgehog signaling. Zebrafish experiments demonstrated a full spectrum of phenotypes associated with defective cilia: Body curvature, kidney cysts, left–right asymmetry, misdirected cilia in the pronephric duct, and retinal defects.